Pendidikan Agama Islam Sebagai Sarana Pembentukan Moral Dan Karakter Siswa - Tsani, Iskandar (Didaktika Religia, 2013)
This article discusses the role of Islamic education in shapping moral and character for students. The goal of Islamic education is to make student close to God and enlightening human being.Â  To make a good character in student life we have to use a right stategy in implementing Islamic education. The goal of implementing Islamic education is to develop values, good habits, and positive attitude to make student getÂ  mature and responsible in the daily life as a result of character and moral performance. .